A robust PID controller based on linear quadratic gaussian approach for improving frequency stability of power systems considering renewables. (November 2021) - Khamies, Mohamed; Magdy, Gaber; Ebeed, Mohamed; Kamel, Salah
Abstract: This paper proposes a novel robust controller for frequency stabilization of electrical systems taken into consideration a high renewable energy sources (RESs) penetration. The suggested controller, robust PID (RPID) controller, is combination of a proportional–integral–derivative (PID) controller and a linear quadratic gaussian (LQG) controller. Furthermore, the Improved lightning attachment procedure optimization (ILAPO) technique is applied for determining the optimal setting of the parameters of the introduced RPID controller. A studied power system with RESs is used as a test system to justify the performance of the RPID controller. The superiority of the introduced robust controller is verified through a comparison of its performance under system uncertainties with those of other robust controllers presented in the literature. The results elucidate that the RPID controller can effectually enhance frequency stability and guarantee reliable performance for power grids supplied with high share of renewable energy for all studied scenarios. Consequently, the proposed RPID controller purveys creditable for modern power systems considering RESs. Highlights: A new robust control strategy for frequency stability improvement of power systems. Considering high share of renewable energy sources. Proposed RPID controller is based PID controller and linear quadratic Gaussian approach. The parameters of RPID controller are optimally determined using ILAPO. The RPID is compared with conventional PID controllers under system uncertainties.